2013
DOI: 10.1038/ismej.2013.38
|View full text |Cite
|
Sign up to set email alerts
|

Chemolithotrophic nitrate-dependent Fe(II)-oxidizing nature of actinobacterial subdivision lineage TM3

Abstract: Anaerobic nitrate-dependent Fe(II) oxidation is widespread in various environments and is known to be performed by both heterotrophic and autotrophic microorganisms. Although Fe(II) oxidation is predominantly biological under acidic conditions, to date most of the studies on nitrate-dependent Fe(II) oxidation were from environments of circumneutral pH. The present study was conducted in Lake Grosse Fuchskuhle, a moderately acidic ecosystem receiving humic acids from an adjacent bog, with the objective of ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 68 publications
2
16
0
Order By: Relevance
“…Cloning and sequencing of both mcrA (Conrad, Klose, Noll, Kemnitz, & Bodelier, ) and archaeal 16S rRNA genes were performed using Marburg feather moss sample‐1 for identification of the T‐RFs and for phylogenetic analysis of the methanogens according to the procedure described before (Kanaparthi et al., ). Neighbor‐joining phylogenetic tree of 16S rRNA gene sequences was constructed using ARB after aligning the sequences with SINA aligner.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cloning and sequencing of both mcrA (Conrad, Klose, Noll, Kemnitz, & Bodelier, ) and archaeal 16S rRNA genes were performed using Marburg feather moss sample‐1 for identification of the T‐RFs and for phylogenetic analysis of the methanogens according to the procedure described before (Kanaparthi et al., ). Neighbor‐joining phylogenetic tree of 16S rRNA gene sequences was constructed using ARB after aligning the sequences with SINA aligner.…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted from the moss samples using the Soil DNA extraction kit (Machery-Nagel, D€ uren, Germany) according to the manufacturer's instructions. The community finger print was determined by terminal restriction fragment length polymorphism (T-RFLP) as described before (Kanaparthi, Pommerenke, Casper, & Dumont, 2013). In brief, PCR amplification of 16S rRNA gene was performed using FAM labeled ARCH109-F and ARCH934-R primers (Grosskopf, Janssen, & Liesack, 1998).…”
Section: Methanogenic Community Composition and Abundancementioning
confidence: 99%
See 1 more Smart Citation
“…Initially, the division was conducted to enable wholelake experiments in food-web manipulation (Kasprzak, 1993;Koschel, 1995). Over the decades of division, research in Lake Grosse Fuchskuhle has covered several other topics: plankton studies (Glöckner et al, 2000;Hehmann et al, 2001;Macek, Simek, & Bittl, 2001), microorganisms and microbial activity (Grossart et al, 2008;Kanaparthi, Pommerenke, Casper, & Dumont, 2013;Simek et al, 1998), basic limnology and geographical settings (Burkert et al, 2004;Kasprzak, 1993;Koschel, 1995;Richter, 1997;Succow & Jeschke, 1986), and CH 4 and CO 2 cycle (Casper et al, 2003;Chan, Wolf, Hepperle, & Casper, 2002;Conrad, Claus, & Casper, 2010), among others. The two most contrasting basins, namely south-west basin (SW) (characterised by a low pH of 4.4 and DOC of 37.3 mg/L) and the north-east basin (NE) (with a pH of 6.5 and DOC of 16.4 mg/L), were selected for this study (Figure 1).…”
Section: Study Site and Sampling Strategymentioning
confidence: 99%
“…In the absence of photosynthesis, the food chain in the vent system relies on chemoautotrophic prokaryotes, which produce complex organic molecules with energy obtained by oxidizing the inorganic compounds available in the environments. Studies have shown that some chemoautotrophic microorganisms, such as Thioreductor, Sulfurovum, and Sulfurimonas, can use reduced sulfur compounds, Fe(II), Mn(II), H 2 , and CH 4 as electron donors to obtain energy and fix carbon, thus providing a basis for hydrothermal vent ecosystems (Biddle et al 2012;Inagaki et al 2004;Kanaparthi et al 2013;Mino et al 2014;Nakagawa et al 2005a). In addition, heterotrophic bacteria were also rich in hydrothermal systems (Rajasabapathy et al 2014), and they play important roles in carbon and nitrogen cycling by decomposing particulate organic materials (Zhou et al 2009a, b).…”
Section: Introductionmentioning
confidence: 99%